Tracers - Howard, J. J. (Jennifer Jane), 1972- (G.P. Putnam's Sons, an imprint of Penguin Group (USA), 2015)
"Cam is a New York City bike messenger with no family or strings attached to anyone, but when he meets a mysterious stranger and is pulled into her dangerous world of parkour, he is torn between following his heart and sacrificing everything to pay off his debts"--